Konsep Ikhlas dalam Al-Qur‘An - Miss Rosidah Haji Daud; Salman Abdul Muthalib; Muslim Djuned (TAFSE: Journal of Qur'anic Studies, 2017)
The Qur'an is the holy book of Muslims which is the guide and guidance of human life both as individuals and in groups. One of the solutions offered by the Qur'an in living life is with a sincere attitude, sincerity is the basis for accepting human deeds. While a phenomenon in this modern era, many people are found who tend to view that life is not free, there is always a fee to be paid, this makes them always take into account profit and loss in all aspects of their work, and this situation leads to the difficulty of an action. that humans do sincerely. Therefore, the study of sincerity has its own urgency, so humans do not always measure success with the material they receive. This research is a literature study that wants to explain the meaning of sincerity contained in the Qur'an and the Prophet's hadith. Data was collected through thematic methods and analyzed descriptively. The results of the study indicate that sincerity is an act based on motivation to gain the pleasure of Allah swt. Sincerity is the main condition for the acceptance of an act of worship. Without sincerity, any amount of worship will not reach Allah and even be classified as a useless charity. Al-Qur‘an adalah kitab suci umat Islam yang menjadi pedoman dan tutunan hidup manusia baik sebagai individu maupun berkelompok. Salah satu solusi yang ditawarkan al-Qur‘an dalam menjalani hidup adalah dengan sikap ikhlas, ikhlas merupakan dasar diterimanya amal perbuatan manusia. Sementara fenomena di era modern ini, banyak ditemukan manusia yang cenderung memandang bahwa hidup ini tidak ada yang gratis, selalu ada biaya yang harus dibayar, hal ini yang menjadikan mereka selalu memperhitungkan untung rugi dalam segala aspek pekerjaannya, dan keadaan ini mengarah kepada sulitnya suatu perbuatan yang dilakukan manusia secara ikhlas. Oleh karena itu, kajian tentang ikhlas memiliki urgensi tersendiri, sehingga memuat manusia tidak selalu mengukur keberhasilan dengan materi yang dia terima. Penelitian ini bersifat kepustakaan yang ingin menjelaskan makna ikhlas yang terkandung dalam al-Qur’an dan hadis Nabi. Data yang dikumpulkan melalui metode tematik dan dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa ikhlas merupakan perbuatan yang berlandaskan motivasi untuk memperoleh keridhaan Allah swt. Ikhlas adalah syarat utama diterimanya sebuah amal ibadah. Tanpa keikhlasan, amal ibadah sebesar apapun tidak akan sampai kepada Allah dan bahkan tergolong sebagai amal yang sia-sia.